Sensorless finite-control set model predictive control for IPMSM drives - Rovere, Luca; Formentini, Andrea; Gaeta, Alberto; Zanchetta, Pericle; Marchesoni, Mario (Institute of Electrical and Electronics Engineers, 2016)
This paper investigates the feasibility of a sensorless field oriented control (FOC) combined with a finite control set model predictive current control (FCS-MPC) for an interior permanent magnet synchronous motor (IPMSM). The use of a FCS-MPC makes the implementation of most of the existing sensorless techniques difficult due to the lack of a modulator. The proposed sensorless algorithm exploits the saliency of the motor and the intrinsic higher current ripple of the FCS-MPC to extract position and speed information using a model-based approach. This method does not require the injection of additional voltage vectors or the periodic interruption of the control algorithm and consequently it has no impact on the performance of the current control. The proposed algorithm has been tested in simulation and validated on an experimental set-up, showing promising results.